Layered adsorbent structure
Photopolymerization additive manufacturing enables the production of strong, complex-shaped molded adsorbents by forming multiple layers of photopolymerized resin with adsorbent materials, addressing the limitations of conventional methods in achieving desired shapes and strength.
Patent Information
- Application Number
- JP2021569571
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-27
- Filing Date
- 2020-06-05
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2040-06-05
AI Technical Summary
Conventional methods for producing molded adsorbents, such as getters, are limited by the shapes that can be achieved and the insufficient strength of adsorbents made using powder-based methods.
The use of photopolymerization additive manufacturing to create molded adsorbents with complex shapes by combining adsorbent materials with a photopolymer and forming multiple layers of photopolymerized resin through controlled exposure to electromagnetic radiation.
This method allows for the creation of adsorbents with enhanced strength and complex geometries, effectively capturing unwanted materials while maintaining structural integrity.
Smart Images

Figure 0007650577000004 
Figure 0007650577000005 
Figure 0007650577000006
Abstract
Description
[Technical field]
[0001] FIELD OF THEINVENTION The present invention relates to shaped adsorbents, and in particular to shaped getters. [Background technology]
[0002] Getters are sorbent compositions that are often used within sealed enclosures that form part of or housing for electrical or electronic devices to remove undesirable substances from the atmosphere within the enclosure.
[0003] Getter compositions are known. For example, US Pat. No. 6,428,612 discloses a hydrogen getter comprising a particulate zeolite having a portion of the sodium ions exchanged by an activating metal such as silver. The getter is provided in a flexible hydrogen-permeable, moisture-impermeable sheet material in combination with a moisture absorbent. US Pat. No. 5,888,925 describes a getter comprising an effective amount of an oxide of a platinum group metal, a desiccant, and a gas-permeable binder, preferably compounded and cured in an oxygen-bearing environment at about 150 to about 205° C. US Pat. No. 4,559,471 describes the use of a getter support for decomposing hydrocarbons in a vacuum device, where the getter support comprises an inorganic porous support loaded with one or more of rhodium, copper, platinum, palladium, and their oxides. US Pat. No. 6,200,494 describes a combination of getter materials comprising a mixture of an oxide of a transition metal, metallic palladium, and a moisture-absorbing material. Getters for moisture are also known. WO 02 / 43098 describes a getter for use in a sealed enclosure in the form of a porous body formed from particles of FAU zeolite having a silica to alumina molar ratio of less than 10, and particles of a high silica to alumina molar ratio zeolite having a silica to alumina molar ratio of at least 20, both bound with an inorganic binder. WO 2015 / 015221 discloses a getter composition suitable for gettering hydrogen and moisture, comprising an alkaline earth metal oxide or a precursor thereof and a transition metal oxide or a precursor thereof, the transition metal being selected from copper, nickel, and cobalt.
[0004] While prior art getter compositions are useful in many applications, they are limited by the limited shapes that can be achieved using conventional methods. Summary of the Invention [Problem to be solved by the invention]
[0005] Additive manufacturing (ALM), also known as three-dimensional (3D) printing, is an evolving technology that offers the ability to create new shapes. WO 2012 / 032325 discloses a method for manufacturing catalysts using additive manufacturing, including (i) forming layers of powder catalyst or catalyst support material, (ii) bonding or fusing the powders in such layers according to a predetermined pattern, (iii) repeating (i) and (ii) layers on layers to form shaped units, and (iv) optionally applying catalyst material to such shaped units. However, the strength of shaped adsorbents made using powder-based methods is insufficient to prepare getters.
[0006] Applicants have discovered that photopolymerization additive manufacturing surprisingly provides a means to prepare new adsorbents whose shapes are not dictated by traditional molding techniques.
[0007] Thus, the present invention provides a shaped adsorbent comprising multiple layers of a photopolymerized resin containing particles of an adsorbent material.
[0008] The present invention further provides a method of making a shaped sorbent, comprising the steps of: (i) combining an adsorbent material with a photopolymer to form an adsorbent mixture; and (ii) using photopolymerization to form a shaped sorbent comprising multiple layers of photopolymerized resin containing particles of the adsorbent material.
[0009] The present invention further provides the use of a shaped adsorbent comprising multiple layers of a photopolymerized resin containing particles of an adsorbent material as a getter.
[0010] The term "adsorbent (sorbent) " includes adsorbents and absorbents.
[0011] The adsorbent material may be any adsorptive or absorbent material, i.e., any material used as an adsorbent to remove substances. The adsorbent may include alumina, silica, carbon, a mixture of two or more of these, or any other suitable adsorbent material. The adsorbent material may include a molecular sieve. The molecular sieve may be a zeolite material, such as Zeolite X, Zeolite Y, ZSM-5, Zeolite 13X, CBV500, 3A Zeolite, or a phosphate-containing molecular sieve, such as aluminum phosphate (ALPO) or aluminum silicoaluminophosphate (SAPO), or any other molecular sieve material. Molecular sieves function at least in part by physically capturing the undesired substance and removing it from the environment. Alternatively, or in addition, the adsorbent material may include a reactive adsorbent, i.e., an adsorbent material that chemically reacts with the undesired substance. The reactive adsorbent material may include one or more transition metal compounds, rare earth metal compounds, alkali metal compounds, or alkaline earth metal compounds. One or more of these compounds may be present. Suitable transition metal compounds include compounds of copper, zinc, cobalt, nickel, iron, platinum, and palladium. Metal oxides and / or metal hydroxides are most preferred in the present invention.
[0012] The shaped adsorbent may include one or more molecular sieve adsorbent materials and one or more reactive adsorbent materials.
[0013] Maximum of adsorbent material in molded adsorbent Particle size (Dv100) is preferably less than the layer thickness, more preferably less than half the layer thickness, most preferably less than one fifth of the layer thickness, in particular less than one tenth of the layer thickness. For example, for a layer thickness of 10 μm, the maximum Particle size can be in the range of 1 to 10 μm. Similarly, for a layer thickness of 100 μm, a maximum Particle size may be in the range of 10 to 100 μm. For layers having a thickness of more than 100 μm, a maximum Particle size can be larger, but this is not required.
[0014] In the molded adsorbent Particle sizecan be determined using an X-ray microscope.
[0015] The molded sorbent includes multiple layers of photopolymerized resin, each layer containing particles of sorbent material. Applicants have surprisingly found that the sorbent material encapsulated within the multiple layers of photopolymerized resin can effectively capture substances during use despite being contained within the resin.
[0016] Photopolymerization generally refers to the curing of a liquid photoreactive polymer (alternatively known as a photopolymer) by ultraviolet or visible light or another form of electromagnetic radiation to form a photopolymerized resin. The liquid photoreactive polymer reacts under the action of a light source, for example a UV light source with a wavelength preferably in the range of about 375-405 nm, to form a rigid three-dimensional shape. The applicant has found that photopolymerization additive manufacturing based on photolithography is particularly suitable for the production of shaped adsorbents. The most common photolithography-based technique is known as stereolithography (SLA), in which a layer of resin that forms part of the desired overall shape is cured by tracing a two-dimensional image with an ultraviolet laser in a liquid photopolymer bath. Once the tracing is complete, the cured layer is immersed, for example, by lowering a build platform on which the cured layer is supported into the liquid photopolymer bath and then repeating the process. The process is repeated layer by layer until the desired shape is formed. Photopolymerization additive manufacturing techniques generally use a bath containing liquid photopolymer, so the technique is sometimes referred to as liquid bath photopolymerization. A window may be provided in the base of the bath to allow a light source to be applied to the photopolymer from below. The laser is controlled by a computer programmed with a predetermined design for the shape. The shaped adsorbent may be conveniently designed using CAD-CAM software, which creates a three-dimensional computer model that is converted into the desired shape. The three-dimensional image is "cut" into slices using the software, and each slice is reconstructed by optical radiation curing of the liquid photopolymer, converting the image into a solid object. The computer and system are commonly provided together as an SLA printer. SLA printers are commercially available.
[0017] A particularly suitable technique similar to SLA is known as Digital Light Processing (DLP), which, rather than tracing a laser beam, uses a projector to project the entire layer of adsorbent molded onto the photopolymer through a window at the base of the reservoir. This reduces the time required to build the layer and allows the build platform to be raised or lowered. A non-sticky layer may be provided on the window to allow removal of the molding unit. Suitable materials include polydimethylsiloxane (PDMS) film or fluorinated ethylene polymer (FEP) film. A particularly suitable FEP film has a thickness of 0.25 mm. A method known as Continuous Liquid Interface Manufacturing (CLIP) or Digital Light Synthesis (DLS) is based on DLP, but instead of using a non-sticky polymer to physically separate the cured layer from the liquid photopolymer, CLIP creates an oxygen-containing zone at the build point where a thin uncured liquid layer is formed, thereby avoiding adhesion of the molding unit to the window. The platform may be lowered from the cured layer, or the cured layer may be raised from the liquid pool using a build support plate. This approach eliminates the separate steps required by conventional SLA or DLP printers and reduces the production time of layered structures. A description of the photopolymerization process and equipment can be found in "Additive Manufacturing Technologies - Rapid Prototyping to Direct Digital Manufacturing" by Ian Gibson, David W. Rosen and Brent Stucker, Spring (2010). CLIP is described in more detail in Tumblestone, et al in Science, 347 (2015) pages 1349-1352.
[0018] Other additive manufacturing techniques may be used, such as material jetting. Material jetting is based on the principles of a conventional inkjet printer, but uses photocurable resins instead of conventional inks. Two resists are used: the build material and the support material. The support material is subsequently removed after the features have been formed. This extra complexity, and the constraints on the physical properties of the adsorbed mixture due to the need for jetting, make material jetting less preferred than digital light processing and continuous liquid interface manufacturing or digital light synthesis methods.
[0019] Preferably, the molded sorbent is subjected to a post-molding treatment to ensure completion of the reaction, such as placing the molded sorbent in a UV chamber to complete the curing process.
[0020] The photopolymers used in the present invention may be any suitable liquid photopolymer that hardens or cures when exposed to light in the ultraviolet or visible regions of the electromagnetic spectrum. Most commonly, photopolymerized systems are typically cured by ultraviolet light, as ultraviolet light is more energetic, but the development of dye-based photoinitiator systems has allowed the use of visible light, with the potential advantage of being a safer process to handle. Photopolymers often contain a mixture of monomers, oligomers, and photoinitiators that are formed into a hardened polymeric material through a process called curing. Typically, photopolymers contain a mixture of multifunctional monomers and oligomers to achieve the desired physical properties, and thus a wide variety of monomers and oligomers have been developed that can polymerize in the presence of light via internal or external initiation. The properties of the photocured material, such as flexibility, adhesion, and chemical resistance, are provided by the functionalized oligomers present in the photocurable composite. The oligomers are typically epoxides, urethanes, polyethers, or polyesters, each of which provides specific properties to the resulting material. Each of these oligomers is typically functionalized with an acrylate. Curing forms what is known as a network polymer. Photopolymers often contain a photoinitiator. A photoinitiator is a compound that upon irradiation with light breaks down into reactive species that activate polymerization of specific functional groups on the oligomer. There are two general pathways for photoinitiation, either of which may be used: free radical and ionic. Electron beam curing is possible for reactive oligomers and monomers that do not contain a photoinitiator, but this method is preferred.
[0021] Suitable photopolymers include acrylate oligomers that can be used in combination with a wide range of reactive monomers or other oligomers and photoinitiators to produce photopolymerized resins. The photopolymer must have sufficient crosslinking and should ideally be designed to have minimal volumetric shrinkage upon polymerization to avoid distortion of the molded adsorbent. Common monomers utilized in imaging include multifunctional acrylates and methacrylates, often combined with non-polymeric components to reduce volumetric shrinkage. Competitive complex mixtures of epoxide resins and cationic photoinitiators are increasingly being used because they have significantly lower volumetric shrinkage upon ring-opening polymerization than acrylates and methacrylates. Free radical and cationic polymerizations of both epoxide and acrylate monomers may also be used, offering high polymerization rates from the acrylic monomers and better mechanical properties from the epoxy matrix. Suitable photopolymers are commercially available.
[0022] If desired, light blocking compounds such as dyes may be included in the adsorption mixture to modify the cure rate and aid in the molding process.
[0023] The viscosity of the photopolymers for use in preparing the adsorption mixtures and shaped adsorbents is desirably within the range of 1 to 500 mPa·s at 20°C, preferably within the range of 1 to 250 mPa·s at 20°C, and more preferably 1 to 100 mPa·s at 20°C.
[0024] The adsorbent material is mixed with a photopolymer to form a liquid adsorbent mixture that is cured to form a shaped adsorbent. Thus, the method includes (i) forming an adsorbent mixture including a photopolymer and an adsorbent material, (ii) exposing the adsorbent mixture to electromagnetic radiation according to a predetermined pattern to form layers of cured polymer, and (iii) repeating step (ii) for each layer to form a shaped product.
[0025] The amount of adsorbent material in the adsorption mixture and in the immediately prepared shaped adsorbent may range from 1 to 70% by volume. A low content in the range of 1 to 20% by volume may be effective in capturing low concentrations of contaminants over an extended period of time. A high content in the range of 20 to 70% by volume, preferably 25 to 70% by volume, increases performance. Applicant has found that above 70% by volume, the viscosity of the mixture is too high to allow rapid formation of a layered structure.
[0026] Determination of the volume percentage can be readily accomplished from the weight and density of the adsorbent material.
[0027] Applicants have found that it is desirable to reduce the viscosity of the adsorbent mixture by including a dispersant in the photopolymer mixture to disperse particles of the adsorbent material and improve processing of the formed adsorbent. The dispersant may be any suitable dispersant, such as anionic dispersants, cationic dispersants, and non-ionic dispersants, that does not interfere with the photopolymer curing process.
[0028] The applicant has found that the temperature of the adsorption mixture can be adjusted before and during molding to reduce the viscosity. The temperature of the adsorption mixture during the molding process is preferably in the range of 20-90°C, more preferably 35-90°C, and most preferably 40-60°C.
[0029] Other means for reducing the viscosity of the adsorption mixture can be used, for example, by including a low viscosity inert liquid that is removed after curing.
[0030] The adsorption mixture desirably has a viscosity in the range of 1 to 20 mPa·s, preferably 1 to 10 mPa·s, at the temperature used.
[0031] A pore former may also be included to provide porosity to the shaped adsorbent.
[0032] The molded adsorbent comprises multiple layers. The number of layers in the molded adsorbent depends on the resolution of the photopolymerization method and the size of the molded adsorbent, but may range from 5 to 5000 or more in a multi-layer structure. The thickness of the layers in the molded adsorbent comprising multiple layers may range from 10 to 300 μm, but is preferably 20 to 100 μm. SLA, DLP and CLIP techniques are particularly suitable for producing layered structures. Methods providing concentric layers can also be used.
[0033] There is virtually no limit to the geometric shapes of shaped sorbents that can be produced using ALM technology. The shapes can range from skeletal frames or multi-strut lattice structures to faceted robust structures with multiple features. For example, the shaped sorbent can be in the form of a wire frame or skeletal framework structure that contains internal voids and may have multiple internal reinforcing rods, or the shaped sorbent can be a solid unit such as a honeycomb of any shape, or a cylinder, which can be configured to have flat or domed ends, multiple lobes, and / or through holes.
[0034] Lattice framework structures are preferred and may include one or more faces which may be circular or polygonal in shape.
[0035] The shaped sorbent may include one or more through holes, which may be circular, elipsoid, or polygonal in cross section, e.g., triangular, square, rectangular, or hexagonal. The through holes may include two or more parallel running through holes, or non-parallel through holes that run through the shaped sorbent at various angles to the longitudinal axis of the shaped sorbent. Curved through holes, which are not currently possible using conventional pelletizing and extrusion techniques, can also be produced using ALM techniques.
[0036] The shaped sorbent desirably has a high geometric surface area to maximize the surface area for adsorption. For example, the shaped sorbent may have a cylindrical or three-dimensional elliptical shape including through holes, for example as disclosed in WO 2016 / 166523 and WO 2016 / 166526. Particularly suitable shaped sorbents are in the form of open cylinders including a lattice structure or layers of spaced parallel struts or meshes. The cylinders preferably have an aspect ratio, i.e., length / diameter, of ≦1, for example 0.10 to 0.75.
[0037] The shaped adsorbent may have a cross-sectional size (either length width or height) ranging from 0.3 mm to 100 mm, preferably from 0.3 mm to 50 mm.
[0038] The shaped sorbent may further include lugs or tabs that allow it to be secured during use.
[0039] The shaped adsorbent may alternatively be formed as a multi-channel monolith or honeycomb structure, which may have widths or lengths ranging from 10 cm to 250 cm.
[0040] The molded sorbents may be used in processes for removing substances from sealed enclosures that may contain gases, liquids, or inert gases such as nitrogen or argon under vacuum. The molded sorbents are very thermally stable, but gettering is typically performed at temperatures ranging from 0 to 60°C. The invention is particularly useful for the manufacture of molded getters for removing one or more undesirable substances from sealed enclosures, particularly hermetically sealed enclosures. The molded sorbents may be used to remove one or more of water vapor, carbon monoxide, carbon dioxide, hydrogen sulfide, hydrogen chloride, oxygen, ammonia, hydrogen, organic molecules such as methanol or ethanol, or hydrocarbons such as methane, ethane, or ethylene. The molded sorbents are particularly useful for removing water vapor and hydrogen. Thus, the invention includes a process for removing substances from an environment by contacting the environment with a molded sorbent comprising one or more layers of a photopolymerized resin containing particles of an adsorbent material. [Brief description of the drawings]
[0041] The invention will now be further described with reference to the following figures. [Figure 1] FIG. 1 is a diagram of the liquid vat additive manufacturing (VP-ALM) apparatus used to prepare shaped adsorbents. [Diagram 2] FIG. 1 is a side view of a shaped getter prepared using the apparatus. [Diagram 3] FIG. 2 is a top view of the same molded sorbent. [Figure 4] 1 showing the layers in the shaped adsorbent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0042] Example 1. Preparation of shaped zeolite adsorbents by digital light processing Materials and Equipment. Adsorbent materials: 3A zeolite powder and PdO powder (both commercially available).
[0043] Photopolymer: CPS2030. CPS2030 is a formulated commercial product containing a photoinitiator and a polymer precursor. The viscosity of the photopolymer at 20° C. was 30 mPa·s. This photopolymer is available from Colorado Photopolymer Solutions.
[0044] Dispersant: Hypermer™ KD1 is a cationic polymeric dispersant. This material is available from Croda™.
[0045] Computer-aided design equipment: a desktop computer running "Blender" open source software, followed by refinement of the structure using "Element" software available from nTopology.
[0046] DLP printer device: Moonray™ S available from Sprintray Inc. The device is shown in FIG. 1. The device comprises a computer control unit (not shown) that controls the device, and a tank or reservoir 10 for the adsorption mixture with a wall 12 and a glass window 14 at its base to allow light from a computer controlled digital light processor 16 to be projected using a mirror 18 on the underside of the glass window 14. The reservoir side of the glass window has a non-sticky polymer film 20 placed on it to allow separation of the cured material. A build platform 22 is placed in the liquid adsorption mixture 24 such that there is a liquid layer between the underside of the build platform 22 and the non-sticky polymer film 20. Once a cured layer 26 has been formed, the platform 22 and tank 10 are separated by a layer thickness and the process is repeated. The Moonray™ S can produce layer thicknesses of 20, 50, or 100 μm.
[0047] Preparation of the adsorption mixture: 65 wt.% zeolite 3A in CPS2030 / Hypermer™ KD1.
[0048] 98g of CPS2030 was weighed out and warmed to 50°C. Hypermer™ KD1 was warmed to 50°C to ensure it was liquid before adding to the warm CPS2030 resin. 2g of Hypermer™ KD1 was added to 98g of CPS2030 and mixed in a Hauschild Speedmixer™ at 2000 rpm for 180 seconds. 153.29g of 3A Zeolite was weighed out and placed in the Speedmixer™ pot. 88.2g of the previously prepared 2% Hypermer™ KD1 in CPS2030 resin solution was warmed to 50°C and weighed into the Speedmixer™ pot with the powder. The mixture was then placed in the Speedmixer™ and mixed at 1200 rpm for 180 seconds. After mixing, any powder residue was returned from the side of the container and mixed into the bulk mixture. The mixture was then mixed again in the Speedmixer™ at 1200 rpm for 180 seconds. Following this mixing procedure, the adsorbed mixture was poured into the resin tank of a Moonray™ S DLP machine ready to produce molded parts.
[0049] The zeolite 3A was not pre-dried and therefore contained adsorbed water, in these examples the moisture content (determined by measuring the mass loss upon heating to 300° C. for 8 hours) was 18.4 wt %.
[0050] Preparing for DLP printing. The methods and software are commercially available from DLP printer providers or are open source. The methods used herein were as follows. 1. Draw / create the structural design using computer-aided design (CAD) software. 2. Import this structural design into the DLP printer device software for positioning on the virtual build platform and automatic generation of support structures. 3. Generate slice files that divide the design into layers. 4. Send the slice file to the DLP printer device (at this point you should ensure there is adsorbent material mixture in the bath and the build platform is secured if necessary).
[0051] CPS2030 photopolymer solidifies when exposed to light with a wavelength of 405 nm. The power of the Moonray™ S at the curing surface was 2.8 mW·cm-2, calibrated to a peak wavelength of 405 nm. Prior to forming a molded adsorbent, a working curve was determined to identify the exposure to the light source required to produce the desired resolution by exposing the photopolymer to a known amount of energy and then measuring the thickness of the solidified polymer. A description of photopolymerization, including how to determine the working curve, can be found in "Additive Manufacturing Technologies - Rapid Prototyping to Direct Digital Manufacturing" by Ian Gibson, David W. Rosen and Brent Stucker, Spring (2010), pages 61-102.
[0052] Fabrication of shaped sorbents. Referring again to FIG. 1, the adsorption mixture 24 and the firmly fixed build platform 22 were placed in the reservoir 10. The non-tacky FEP polymer film 20 was placed on the glass window 14. The pre-prepared slice file was then processed using a DLP device. Light 28 with a peak wavelength of 405 nm was projected from the digital light processor 16 through the glass window 14 onto the liquid layer in a pattern according to the first layer of molded adsorbent, thereby solidifying it. The projected light is shown by a dotted line in FIG. 1. The reservoir 10 was then lowered or the build platform 22 was raised to allow the liquid to flow between the hardened solidified layer and the non-tacky polymer film 20, and then its position was adjusted to one layer thickness and the process was repeated using the pattern according to the second layer of molded adsorbent, thus building up layers 26 until a fully formed molded adsorbent was obtained. The layer thickness in this example was 100 μm.
[0053] Sample cleaning and post-processing. The molded sorbent was removed from the build platform and washed with isopropanol to remove any unreacted material. The washed molded sorbent was then placed in a UV cure chamber and post-treated at 375-405 nm to fully cure the polymer.
[0054] The shaped adsorbent is shown in FIGS. The molded sorbent shown in Figures 2 and 3 comprises an open cylindrical structure 30 containing an internal lattice structure 32 containing parallel struts. Three equally spaced lugs 34 were provided around the circumference of the cylinder at one end to allow for mounting of the molded sorbent into an apparatus or sealed enclosure. The diameter of the cylinder was 20 mm. The height of the cylinder was 5 mm (hence L / D was 0.25). The lugs 34 were 2.75 mm wide and 1.25 mm high. The strut thickness in the lattice structure was 0.8 mm. Figure 4 shows an enlarged portion of Figure 2 showing that the lattice structure 32 contains multiple layers 36. The number of layers in this molded sorbent was 50.
[0055] Example 2. Dynamic Vapor Sorption (DVS) Testing Tests were performed on the cured sorbent mixture prepared in Example 1, containing 65 wt% Zeolite 3A in 2 wt% Hypermer™ KD1 / CPS2030 photopolymer. Samples for testing were prepared by casting the liquid sorbent mixture onto an FEP-coated glass slide and exposing the resulting layer to a 405 nm light source. Cured molded sorbent samples were prepared with thicknesses ranging from 0.3 to 1 mm. The cured samples were then broken to form flakes of material to fit into a 9 mm sample holder for DVS testing.
[0056] A surface measurement system DVS advantage™ instrument was used to measure moisture sorption using the following procedure: Each sample was preheated at 120° C. for 6 hours and the dehydrated sample mass was recorded. 3 Moisture sorption was measured by mass change of samples exposed to a nitrogen flow of 10000 / min (containing 40% relative humidity at 20° C.) for 480 min. The results were as follows:
[0057] [Table 1]
[0058] The results show that the thinner photopolymerized samples containing zeolite are more capable of trapping water vapor.
[0059] It is noted that the photopolymerized sample was not saturated at the end of the test period (8 hours). Further measurements performed up to 16 hours showed that it continued to adsorb water at a constant rate, achieving an uptake of 14.3 wt.%.
[0060] Example 3. Preparation of shaped PdO / zeolite adsorbents by digital light processing Shaped adsorbent samples were prepared using the casting method of Example 2 to test whether they could produce shaped adsorbents that getter hydrogen. Adsorbent mixtures were prepared by mixing 5 wt % or 10 wt % PdO powder (sieved to <45 μm) in 2 wt % Hypermer™ KD1 / CPS2030 photopolymer adsorbent mixture prepared in Example 1, in 65 wt % Zeolite 3A, and then molded.
[0061] The hydrogen uptake of the samples was then measured using a Chemisorb 2480 volumetric chemisorption analyzer. Accurately weighed aliquots of approximately 0.5–1 g of material were used. Activation of the samples was performed using a 50 cm 3 This was achieved by flowing compressed air through the sample at 10°C / min from ambient temperature to 120°C, followed by a 2 hour hold at this temperature. At the end of this time, the compressed air was turned off and the sample was allowed to cool to the analysis temperature of 35°C and a pressure of less than 10 µmHg while being released to vacuum. Once these conditions were met, the sample was held under vacuum for a further 60 minutes. Pure hydrogen uptake was measured at 100, 150, 200, 300, 400, 500, 600, 700 and 760 mmHg using a 10 second equilibration time to generate an equilibrium isotherm. The sample weight after measurement was used to calculate the total gas uptake in cm at 760 mmHg. 3 The results were reported as follows:
[0062] [Table 2]
[0063] The formed adsorbent was able to adsorb hydrogen during testing.
[0064] Example 4. Preparation of shaped zeolite adsorbents by digital light processing Materials and Equipment. Adsorption material: 3A zeolite powder.
[0065] Photopolymer: Genesis Flexible Development Base Resin is a commercially available photocurable resin consisting of acrylated monomers / oligomers (urethane acrylate resins and urethane acrylates), dispersants, and photoinitiators. The viscosity of the photopolymer at 20 °C is 45 mPa·s. This photopolymer was supplied by Tethon Corporation Inc and was used as received.
[0066] Computer-aided design equipment: a desktop computer running "Blender" open source software, followed by refinement of the structure using "Element" software available from nTopology.
[0067] Liquid Bath Photopolymerization Additive Manufacturing (VP-ALM) Apparatus: Bison 1000 DLP available from Tethon Corporation Inc. The apparatus is similar to that shown in FIG. 1. The apparatus includes a computer control unit that controls the apparatus, and a computer controlled digital light processor. A bath or reservoir for liquid photopolymer or adsorbent mixture with a thin transparent polymer window at its base to allow light from a light source to be projected using a mirror onto the liquid layer at the bottom of the reservoir. The transparent polymer window is tack-free to allow peeling of the layer of cured material. A build platform is placed in the liquid photopolymer or adsorbent mixture such that there is a liquid layer between the underside of the build platform and the non-tacky polymer film.
[0068] Preparation of the adsorption mixture: 65 wt% Zeolite 3A in Genesis Flexible Development Base Resin. 50.67 g of 3A Zeolite was weighed and placed in a Hauschild Speedmixer™ pot. 27.28 g of Genesis Flexible Development Base Resin was weighed into the Speedmixer pot with the 3A Zeolite. The mixture was then placed in the Hauschild Speedmixer™ and mixed at 2000 rpm for 60 seconds. After mixing, any powder residue was returned from the side of the container and mixed into the bulk mixture. The mixture was then mixed in the Speedmixer™ for 60 seconds at 3000 rpm three more times.
[0069] The zeolite 3A was not pre-dried and therefore contained adsorbed water, in this example the moisture content (determined by measuring the mass loss upon heating to 300° C. for 8 hours) was 18.4 wt %.
[0070] Following this mixing procedure, the adsorbed mixture was poured into the resin tank of a Bison 1000 DLP machine ready to produce molded parts.
[0071] Preparing for DLP printing. The methods and software are commercially available from DLP printer providers or are open source. The methods used herein were as follows. 1. Draw / create the structural design using computer-aided design (CAD) software. 2. Import this structural design into the DLP printer device software for positioning on the virtual build platform and automatic generation of support structures. 3. Generate slice files that divide the design into layers. 4. Send the slice file to the DLP printer device (at this point you should ensure there is adsorbent material mixture in the bath and the build platform is secured if necessary).
[0072] Genesis Flexible Development photopolymer solidifies when exposed to light with a wavelength of 405 nm. The Bison 1000 has light sources with various power outputs. At the curing surface, the power is as low as 2.24 mW cm -2 , maximum 9.05mW cm -2 This was calibrated to a peak wavelength of 405 nm.
[0073] Fabrication of shaped sorbents. The fully assembled reservoir was filled with the adsorbent mixture without the build platform. The pre-prepared slice files were then processed using the DLP device. Light was projected from the digital light processor through a window onto the liquid layer in a pattern according to the first layer of molded adsorbent, thereby solidifying it. After a set exposure time, the light was turned off and the process was repeated using a pattern according to the second layer of molded adsorbent, thus building up layers until a fully formed molded adsorbent was obtained.
[0074] The number of exposures was determined by designing an input file that, when processed into slices by the software, resulted in shaped adsorbents of increasing thickness according to the corresponding number of exposures. Each exposure was for 5 seconds at the respective power setting.
[0075] The layer thickness from each exposure was determined by the material properties of the formulation and the power of the light projector.
[0076] Sample cleaning and post-processing. The molded sorbent was removed from the base of the reservoir and washed with isopropanol to remove any unreacted sorbent material. The washed molded sorbent was then placed in a UV curing chamber and post-treated at 375-405 nm to fully cure the polymer.
[0077] 1 cm x 1 cm squares with thicknesses ranging from 1.0 to 1.5 mm were prepared by this method.
[0078] Example 5. Dynamic Vapor Sorption (DVS) Testing Tests were conducted on an adsorbent containing 65 wt. % zeolite A in Genesis Flexible Development photopolymer, prepared by curing several thin films of the adsorbent mixture according to the procedure of Example 4. Cured molded adsorbent samples with thicknesses of 1.11 (5 layers) and 1.40 mm (10 layers) were used. The cured samples were then broken to form flakes of material to fit into the 9 mm sample holder for DVS testing.
[0079] A surface measurement system DVS Endeavour™ instrument was used to measure moisture sorption using the following procedure: Each sample was preheated at 120° C. for 6 hours and the dehydrated sample mass was recorded. 3 Moisture sorption was measured by mass change of samples exposed to a nitrogen flow of 10000 / min (containing 40% relative humidity at 20° C.) for 360 min. The results were as follows:
[0080] [Table 3]
[0081] The results show that thin photopolymerized samples prepared with this photopolymer are capable of trapping water vapor. The samples were able to take up water more effectively than the sample of Example 2, despite shorter exposure times to 40% RH, lower flow rates in the DVS instrument, and thicker samples. The polymer is also flexible, providing benefits in installation and use. It should be clearly stated that the present invention described above includes the following aspects. First embodiment: A shaped sorbent comprising multiple layers of a photopolymerized resin containing particles of an sorbent material. Second aspect: The shaped adsorbent of the first aspect, wherein the adsorbent material comprises alumina, silica, carbon, or molecular sieve, preferably a zeolitic material. Aspect 3: A shaped adsorbent according to aspect 1 or aspect 2, wherein the adsorbent material comprises a reactive adsorbent material, preferably one or more transition metal compounds, rare earth metal compounds, alkali metal compounds or alkaline earth metal compounds, more preferably compounds of copper, zinc, cobalt, nickel, iron, platinum and palladium. Fourth Aspect: A shaped adsorbent according to any one of the first to third aspects, comprising a molecular sieve adsorbent material and a reactive adsorbent material. Fifth aspect: A shaped adsorbent according to any one of the first to fourth aspects, wherein the maximum particle size (Dv100) (or maximum particle size (Dv100)) of the adsorbent material in the shaped adsorbent is less than the layer thickness, preferably less than half the layer thickness, more preferably less than one-fifth the layer thickness, and most preferably less than one-tenth the layer thickness. Aspect 6: A shaped adsorbent according to any one of aspects 1 to 5, wherein the photopolymerized resin originates from (or is derived from) a photopolymer comprising a mixture of multifunctional monomers and acrylate-functionalized oligomers, and preferably includes a photoinitiator. Seventh aspect: A shaped adsorbent according to any one of the first to sixth aspects, comprising 1 to 70 volume % of the adsorbent material. Eighth embodiment: A shaped adsorbent according to any one of the first to seventh embodiments, comprising 5 to 5000 layers. Ninth aspect: A shaped adsorbent according to any one of the first to eighth aspects, wherein each layer has a thickness in the range of 10 to 300 μm, preferably in the range of 20 to 100 μm. Tenth aspect: A shaped adsorbent according to any one of the first to ninth aspects, wherein the shaped adsorbent has a cross-sectional length width or height in the range of 0.3 mm to 100 mm, preferably 0.3 mm to 50 mm. 11th aspect: A shaped adsorbent according to any one of the first to tenth aspects, wherein the shaped adsorbent is in the form of an open cylinder comprising a lattice structure or layers of spaced parallel struts or mesh, preferably the cylinder having an aspect ratio of ≦1, and more preferably comprising one or more lugs or tabs that enable the shaped adsorbent to be fixed during use. A twelfth aspect: A method of making a shaped adsorbent unit, the method comprising: (i) combining an adsorbent material with a photopolymer to form an adsorbent mixture; and (ii) using photopolymerization to form a shaped adsorbent comprising multiple layers of photopolymerized resin containing particles of the adsorbent material. Aspect 13: The method of aspect 12, wherein said photopolymerization comprises additive manufacturing photopolymerization, preferably comprising stereolithography, more preferably comprising digital light processing or continuous liquid interface manufacturing. Aspect 14: The method of aspect 12 or aspect 13, wherein the method comprises the steps of: (i) forming an adsorbent mixture comprising a photopolymer and an adsorbent material; (ii) exposing the adsorbent mixture to electromagnetic radiation according to a predetermined pattern to form layers of hardened polymer; and (iii) repeating step (ii) for each layer to form the shaped adsorbent. Aspect 15: The method according to any one of aspects 12 to 14, wherein the photopolymer has a viscosity in the range of 1 to 500 mPa·s at 20° C. Aspect 16: The method according to any one of aspects 12 to 15, wherein the adsorption mixture comprises 1 to 70% by volume of the adsorption material. Aspect 17: The method of any one of aspects 12 to 16, wherein the adsorption mixture comprises a dispersing agent. Eighteenth aspect: Use of a shaped adsorbent comprising multiple layers of a photopolymerized resin containing particles of an adsorbent material as a getter. Aspect 19: The use according to aspect 18, wherein the getter is disposed within a sealed enclosure.
Claims
1. 1. A molded sorbent comprising multiple layers of photopolymerized resin containing particles of an adsorbent material, each layer having a range of 10-300 μm, the maximum particle size (Dv100) of the adsorbent material in the molded sorbent being less than the layer thickness, and the photopolymerized resin being a photopolymer derived resin comprising a mixture of multifunctional monomers and acrylate functionalized oligomers.
2. 10. The shaped adsorbent of claim 1, wherein the adsorbent material comprises alumina, silica, carbon, or molecular sieve.
3. 3. The shaped adsorbent of claim 1 or 2, wherein the adsorbent material comprises a reactive adsorbent material.
4. The shaped adsorbent of any one of claims 1 to 3, comprising a molecular sieve adsorbent material and a reactive adsorbent material.
5. 5. The shaped adsorbent according to any one of claims 1 to 4, wherein the maximum particle size (Dv100) of the adsorbent material in the shaped adsorbent is less than half the layer thickness.
6. The shaped adsorbent of any one of claims 1 to 5, comprising 1 to 70 volume percent of the adsorbent material.
7. 7. The shaped adsorbent of any one of claims 1 to 6, comprising from 5 to 5000 layers.
8. A shaped adsorbent according to any one of claims 1 to 7, wherein each layer has a thickness in the range of 20 to 100 µm.
9. 9. The shaped sorbent of any one of claims 1 to 8, wherein the shaped sorbent has a cross-sectional length width or height in the range of 0.3 mm to 100 mm.
10. 10. A method of making a unit of shaped sorbent according to any one of claims 1 to 9, comprising: (i) combining an adsorbent material with a photopolymer to form an adsorbent mixture; and (ii) using photopolymerization to form a shaped sorbent comprising multiple layers of photopolymerized resin containing particles of the adsorbent material, the photopolymerization comprising digital light processing or additive manufacturing photopolymerization including continuous liquid interface manufacturing, each layer having a range of 10-300 μm, and wherein in the shaped sorbent the maximum particle size (Dv100) of the adsorbent material is less than the layer thickness.
11. 11. The method of claim 10, wherein the method comprises the steps of: (i) forming an adsorbent mixture comprising a photopolymer and an adsorbent material; (ii) exposing the adsorbent mixture to electromagnetic radiation according to a predetermined pattern to form layers of hardened polymer; and (iii) repeating step (ii) for each layer to form the shaped adsorbent.
12. The method according to claim 10 or 11, wherein the photopolymer has a viscosity in the range of 1 to 500 mPa·s at 20° C.
13. A method according to any one of claims 10 to 12, wherein the adsorption mixture comprises 1 to 70% by volume of the adsorption material.
14. 10. Use of the shaped adsorbent according to any one of claims 1 to 9 as a getter, said shaped adsorbent comprising multiple layers of photopolymerized resin containing particles of adsorbent material.
Citation Information
Patent Citations
A getter system comprising an active phase intercalated in a porous material dispersed in a low permeability means
JP2009502472A
Catalyst manufacturing method
JP2013537847A
Three-dimensional molding device and three-dimensional molding program
JP2017170648A
Apparatus, system and method for 3D printing
JP2017532433A
Resin powder for solid molding and manufacturing method of solid molding product
JP2018154093A